Atlantic salmon smolts in the Irish Sea: First evidence of a northerly migration trajectory - Barry, James; Kennedy, Richard; Rosell, Robert S.; Roche, William K. (Fisheries Management and Ecology, 2020)
Publication history: Accepted - 1 May 2020; Published online - 9 June 2020 Results from an acoustic telemetry study revealed for the first time a northerly migration route for Atlantic salmon (Salmo salar L.) smolts leaving the east coast of Ireland. Atlantic salmon smolts were tagged in spring 2019 in the Castletown and Boyne rivers. Three tagged smolts registered on disparate deep‐water offshore marine receivers as they travelled northwards out of the Irish Sea through the North Channel. One fish had migrated an estimated 250 km in a period of 32 days. The remaining two individuals were detected on receivers located off the Northern Ireland coast, further corroborating the northward migration of salmon smolts through the Irish Sea. This research was undertaken as part of the COMPASS project supported by the EU INTERREG VA Programme managed by the Special EU Programmes Body (SEUPB).